GOVERNMENT BUDGETARY ALLOCATION AND NIGERIA’S ECONOMY, 2009 – 2018 (Journal of Global Accounting, 2023)
On a yearly basis, government allocates money to different ministries for sole aim of promoting economic growth and development. This study investigates the effect of budget allocation to education sector, agriculture and natural resources on gross domestic products. The study used ex-post facto research design and relied on secondary data collected from Central Bank Statistical Bulleting. The study covered the period of 2009 to 2018. Ordinary linear regression was used to analyze the data collected. The study observed that government spending on education significantly affects economic growth while government spending on agriculture and natural resources does not significantly affect economic growth in Nigeria. Therefore, the study recommends among others that government should ensure that money that is meant for farmers are disbursed to farmers and not hijacked by politicians cum business men. Farmers and herdsmen dispute should be resolved to promote enabling environment for farming that may leads to improving Nigeria economy.
Keywords: Government Allocation; Economic Growth; Education Sector; Agriculture and Natural Resources.